NAD(+) Depletion Is Necessary and Sufficient forPoly(ADP-Ribose) Polymerase-1-Mediated Neuronal Death - Alano, Conrad C. (Society for Neuroscience, 2010)
Poly(ADP-ribose)-1 (PARP-1) is a key mediator of cell death in excitotoxicity, ischemia, and oxidative stress. PARP-1 activation leads to cytosolic NAD(+) depletion and mitochondrial release of apoptosis-inducing factor (AIF), but the causal relationships between these two events have been difficult to resolve. Here, we examined this issue by using extracellular NAD(+) to restore neuronal NAD(+) levels after PARP-1 activation. Exogenous NAD(+) was found to enter neurons through P2X(7)-gated channels. Restoration of cytosolic NAD(+) by this means prevented the glycolytic inhibition, mitochondrial failure, AIF translocation, and neuron death that otherwise results from extensive PARP-1 activation. Bypassing the glycolytic inhibition with the metabolic substrates pyruvate, acetoacetate, or hydroxybutyrate also prevented mitochondrial failure and neuron death. Conversely, depletion of cytosolic NAD(+) with NAD(+) glycohydrolase produced a block in glycolysis inhibition, mitochondrial depolarization, AIF translocation, and neuron death, independent of PARP-1 activation. These results establish NAD(+) depletion as a causal event in PARP-1-mediated cell death and place NAD(+) depletion and glycolytic failure upstream of mitochondrial AIF release.